ROSCAs: Creating Incentives for Micro-Entrepreneurship - Indu Choudhary; Punam Tyagi (Research Parks Publishers, 2022)
In the metropolitan capital of India, there exists a dual economy: an economy where the formal and the informal sources of finance coexist. Despite the RBI directive of financial inclusion, major sections of the society including women are deprived of the delivery of financial services at affordable costs. The problem is found to be more acute for women residing in urbanized villages of Delhi. The present paper focuses on a unique financial instrument, the rotating saving credit association (Rosca, in short) as an enabler in providing venture capital funds for investment to women micro-entrepreneurs. Rosca emerges as a tool of women empowerment intertwined in social relations. Women roscas help its participants to save and borrow depending on their needs and requirement for funds apart from giving them an opportunity to interact and find solutions to their problems. The paper also lends comparison of rosca finance to other formal and informal sources of finance. It highlights the reasons for choice of this particular financial instrument vis-à-vis others. The paper finds that rosca finance is an optimal source of finance for both the savers and the borrowers in a rosca when we take into consideration the constraints faced by the users of this particular source of finance like lack of appropriate physical collateral and problems of asymmetric information.